2019
DOI: 10.12659/msm.915798
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of a Competitive Endogenous RNA Network in Uterine Corpus Endometrial Carcinoma

Abstract: Background: Long non-coding RNAs (lncRNAs) affect post-transcriptional regulation by interfering with microRNAs (miRNAs), and by acting as competitive endogenous RNAs (ceRNAs). The roles and mechanisms of lncRNAs as ceRNAs in the progression and prognosis of uterine corpus endometrial carcinoma are not well understood. Material/Methods: We analyzed high-throughput transcriptome data downloaded from The Cancer Genome Atlas database for 548 patients with uterine corpus endometrial carcinoma, and the we construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The factors that affect endometrial cancer are diverse. First, the instability of estrogen levels is one of the most common causes, so postmenopausal women are more susceptible to endometrial cancer [ 3 ]. Besides, many factors, including smoking, hypertension, overweight, and genetics, play a vital role in the development of endometrial cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that affect endometrial cancer are diverse. First, the instability of estrogen levels is one of the most common causes, so postmenopausal women are more susceptible to endometrial cancer [ 3 ]. Besides, many factors, including smoking, hypertension, overweight, and genetics, play a vital role in the development of endometrial cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they showed that overexpression of LINC00261 reduced β-catenin and TCF4 expression and simultaneously increased E-cadherin, which is a TCF4 downstream target. In addition, other studies suggested that LINC00261 might act as a sponge for several miRNAs, as it was found in several comprehensive analyses of ceRNA networks in different types of cancer [73][74][75]. However, stringent experimental evidence that would clearly support a ceRNA function of LINC00261 is still lacking.…”
Section: Discussionmentioning
confidence: 97%
“…A single miRNA can regulate multiple target RNAs that contain the specific miRNA response element and these RNAs can be regulated by multiple miRNAs lay the foundation for the construction of a ceRNA network [ 12 ]. Recent studies have shown novel roles of ceRNA network in lung cancer, breast cancer, gastric cancer, esophageal adenocarcinoma, esophageal squamous cell carcinoma, cholangiocarcinoma, ovarian cancer, and uterine corpus endometrial carcinoma [ 13 – 21 ]. In addition, a previous study has constructed a ceRNA network and predicted the prognosis of soft tissue sarcoma recurrence [ 22 ].…”
Section: Introductionmentioning
confidence: 99%